Caspase Inhibition Reduces Hepatic Tissue Factor-Driven Coagulation In Vitro and In Vivo. (7th December 2017) - Kopec, Anna K; Spada, Alfred P; Contreras, Patricia C; Mackman, Nigel; Luyendyk, James P
Abstract: Tissue factor (TF) is the primary activator of the blood coagulation cascade. Liver parenchymal cells (ie, hepatocytes) express TF in a molecular state that lacks procoagulant activity. Hepatocyte apoptosis is an important feature of acute and chronic liver diseases, and Fas-induced apoptosis increases hepatocyte TF procoagulant activity in vitro . We determined the impact of a pan-caspase inhibitor, IDN-7314, on hepatocyte TF activity in vitro and TF-mediated coagulation in vivo . Treatment of primary mouse hepatocytes with the Fas death receptor ligand (Jo2, 0.5 μg/ml) for 8 h increased hepatocyte TF procoagulant activity and caused release of TF-positive microvesicles. Pretreatment with 100 nM IDN-7314 abolished Jo2-induced caspase-3/7 activity and significantly reduced hepatocyte TF procoagulant activity and release of TF-positive microvesicles. Treatment of wild-type C57BL/6 mice with a sublethal dose of Jo2 (0.35 mg/kg) for 4.5 h increased coagulation, measured by a significant increase in plasma thrombin-antithrombin and TF-positive microvesicles. Total plasma microvesicle-associated TF activity was reduced in mice lacking hepatocyte TF; suggesting TF-positive microvesicles are released from the apoptotic liver. Fibrin(ogen) deposition increased in livers of Jo2-treated wild-type mice and colocalized primarily with cleaved caspase-3-positive hepatocytes. Pretreatment with IDN-7314 reduced caspase-3 activation, prevented the procoagulant changes in Jo2-treated mice, and reduced hepatocellular injury. Overall, the results indicate a central role for caspase activity in TF-mediated activation of coagulation following apoptotic liver injury. Moreover, the results suggest that liver-selective caspase inhibition may be a putative strategy to limit procoagulant and prothrombotic changes in patients with chronic liver disease.